A Encarnação : discussões sobre elementos transformadores da estética da música contemporânea de concerto - Mendes, Adergildo Cardoso (2011)
Contemporary music concert incorporates in its aesthetic a series of musical elements that acted as the object's own transformation and determine directions unanticipated to the route it stood. We'll see, starting from three main elements (tone, tempo and rhythm) developments and relations that take place within the manufacturing process in which the music was submitted and which were the starting point for composing a duo for flute and piano, whose title is "The Incarnation". The musical structure of this work was developed from reading the documents in question and this work aims to establish a parallel between the existing theoretical discussions on the subject, and analysis of the works composed as part of transforming elements in the music of the twentieth century. Key-